Geopolymer material prepared from solid waste in low-alkali environment and preparation method of geopolymer material

By using calcined shell powder, alkali slag powder and granulated blast furnace slag powder to prepare geopolymer materials in a low-alkali environment, the problems of equipment damage, personal burns and high costs caused by the existing strong alkali environment are solved, and high strength is achieved , low-cost and environmentally friendly geopolymer preparation.

CN119330644AInactive Publication Date: 2025-01-21RES INST OF HIGHWAY MINIST OF TRANSPORT +1

Patent Information

Application Number
CN202411272699.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2025-01-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing local polymer preparation technologies are all stimulated by strong alkaline environment, which leads to high risk of equipment damage and high cost, and lacks solutions for low alkaline environment excitation.

Method used

Geopolymer materials are prepared in a low-alkali environment, using calcined shell powder and alkali slag powder as low-alkali excitation materials, combined with granulated blast furnace slag powder as a precursor material, and forming a geopolymer slurry through dry mixing and stirring processes.

Benefits of technology

While reducing energy consumption and costs, it also improves the strength of geopolymers, reduces damage to construction equipment and the risk of personal burns, and solves the problem of solid waste environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119330644A_ABST
    Figure CN119330644A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of geopolymer materials, in particular to a geopolymer material prepared from solid waste in a low-alkali environment and a preparation method of the geopolymer material, and the geopolymer material comprises the following components in parts by weight: 70-100 parts of a geopolymer precursor; 150 to 230 parts of a low alkali excitation material; wherein the low-alkali-excitation material comprises calcined shell powder, alkali residue powder and water, and compared with the prior art, the geopolymer has the beneficial effects that (1) the geopolymer is prepared in a weak-alkali-excitation environment, and weak-alkali-excitation reactants are solid wastes, so that the problem of environmental pollution caused by the solid wastes is solved; a weak base excitation environment can reduce damage to construction equipment, and meanwhile, the risk of burning a human body in the stirring process is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of geopolymer materials, and in particular to a geopolymer material prepared from solid waste in a low-alkali environment and a preparation method thereof. Background Art

[0002] Shells are the outer shells of molluscs living near water. They are formed by the secretion of a special glandular cell of the molluscs to protect the soft parts of the body. They are mainly composed of calcium carbonate. Shells are usually directly discarded or piled up as waste, which not only occupies a large amount of land resources, but also causes serious environmental pollution in coastal areas.

[0003] Alkali residue is the alkaline waste residue discharged during the industrial production of alkali and alkali treatment, mainly including the waste residue discharged during the ammonia-soda process and other industrial production processes. The pH value of alkali residue is generally around 10, showing a medium-strong alkalinity. The main components are calcium carbonate and calcium sulfate. Alkali residue is generally treated by surface accumulation. The annual production of alkali by the ammonia-soda process in my country can reach 4.21 million tons, generating 1.2 million tons of alkali residue waste.

[0004] Geopolymer is a new type of industrial building material made of clay minerals or industrial waste (such as slag, fly ash, clay, volcanic ash, etc.) and alkaline activators, which are processed by appropriate processes. Due to its wide range of raw materials, its production process consumes less energy and emits less carbon. Unlike the cement setting process, the geopolymer solidification process is a process in which the -O-Si-O-Al-O-bond in the silicate material breaks and re-condenses to form a tetrahedral mesh structure, which makes the generated material have a fast setting time and high early strength. It also has the advantages of high temperature resistance, small shrinkage, and excellent durability. However, the existing geopolymer preparation and construction technology all adopts strong alkaline environment excitation. Since the storage and preparation of alkaline activators are not considered, the extremely corrosive nature of the flake caustic soda that creates a strong alkaline excitation environment will damage the mixing equipment and there is a risk of splashing to the person and causing burns during the mixing process, which is not conducive to construction and has high costs. Therefore, considering the use of low-alkali environment to excite geopolymer materials has obvious social and economic benefits.

[0005] Therefore, developing a geopolymer material and preparation method prepared from solid waste in a low-alkali environment not only has urgent research value, but also has good economic benefits and industrial application potential, which is the driving force and basis for the completion of the present invention. Summary of the invention

[0006] In order to overcome the above-mentioned defects of the prior art, the inventors conducted in-depth research and completed the present invention after paying a lot of creative work.

[0007] Specifically, the technical problem to be solved by the present invention is to provide a method for preparing geopolymer materials using solid waste, thereby improving the strength of the geopolymer while reducing energy consumption and cost and solving environmental problems.

[0008] To achieve the above object, the present invention provides the following technical solutions:

[0009] A geopolymer material prepared in a low-alkali environment, wherein the geopolymer material has the following composition and proportions by weight:

[0010] 70-100 parts of geopolymer precursor;

[0011] 150-230 parts of low-alkali exciting material;

[0012] The low-alkali activating material includes 50-80 parts of calcined shell powder, 50-80 parts of alkali residue powder, and 50-70 parts of water.

[0013] The geopolymer precursor is a high aluminosilicate volcanic ash material.

[0014] In the present invention, as an improvement, the geopolymer precursor includes one or more of metakaolin, slag powder, fly ash or red mud in high aluminosilicate volcanic ash materials.

[0015] In the present invention, as an improvement, the slag powder in the high aluminosilicate volcanic ash is granulated blast furnace slag powder, and the 7-day activity index of the slag powder is greater than 75, and the 28-day activity index is greater than 95.

[0016] A method for preparing geopolymer in a low-alkali environment comprises the following steps:

[0017] Preparation of shell powder

[0018] The cleaned shells are dried, crushed, and ground, and then calcined at 650°C for 4-5 hours to obtain calcined shell powder;

[0019] Preparation of alkali slag powder

[0020] The alkali residue is dried at 105°C for 4-6 hours, put into a grinder, and sieved to obtain alkali residue powder;

[0021] Geopolymer preparation

[0022] Pour shell powder and alkali residue powder into a mixing container in a certain proportion, dry mix for 3 minutes, add water and stir until uniform, to obtain a low-alkali excitation solution;

[0023] Add the geopolymer precursor to the low-alkali activated solution and stir for 3-5 minutes until a geopolymer slurry with a uniform texture is obtained.

[0024] In the present invention, as an improvement, the shells are washed and dried at 105°C for 5-6 hours, and then initially crushed by a crusher and passed through a 5.0 mm sieve. The sieved shells are ground by a grinder until all pass through a 0.075 mm sieve to obtain shell powder, and the shell powder is calcined at high temperature to obtain calcined shell powder, wherein the main components of the calcined shell powder are calcium oxide and calcium carbonate.

[0025] In the present invention, as an improvement, the alkali residue is ground by a grinder and then passed through a 0.075 mm sieve until all of it is sieved to obtain alkali residue powder.

[0026] In the present invention, as an improvement, the shell powder and the alkali residue powder are put into a stirring container at a mass ratio of 1:1 for dry mixing.

[0027] A geopolymer material prepared from solid waste has the components in weight fractions as described above, wherein the geopolymer precursor is slag powder.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] (1) The purpose of the present invention is to provide a weak base excitation environment for preparing geopolymers, and the weak base excitation reactants are all solid wastes. While solving the problem of solid waste environmental pollution, the weak base excitation environment can reduce damage to construction equipment and reduce the risk of burns to people during the mixing process.

[0030] (2) The present technical solution uses granulated blast furnace slag powder as a precursor material to prepare geopolymers. The granulated blast furnace slag powder is inexpensive and is also a waste material generated by industrial development. Its high calcium content can form CHS single-chain gel during the geopolymer solidification process, so its coagulation time is short and its early strength development is fast. The alkaline excitation sources used in the present technical solution are shells and alkaline slag, which are solid wastes generated by industry or other industries. Compared with the existing solid waste treatment technology, the present technical solution can solve the problem of solid waste occupying land resources and polluting the environment, and can effectively reduce the material cost of geopolymer materials in the construction process. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the following is a brief introduction to the drawings required for the specific embodiments or the description of the prior art. In all the drawings, similar elements or parts are generally identified by similar reference numerals. In the drawings, the elements or parts are not necessarily drawn according to the actual scale.

[0032] Figure 1 This is a schematic diagram of the curing days and strength variation trend of the specimens in Example 1 of the present invention;

[0033] Figure 2This is a schematic diagram of the curing days and strength variation trend of the specimens in Example 2 of the present invention;

[0034] Figure 3 Schematic diagram of the curing days and strength change trend of the specimens in Example 3 of the present invention. DETAILED DESCRIPTION

[0035] The following embodiments of the technical solution of the present invention are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present invention, and are therefore only used as examples, and cannot be used to limit the protection scope of the present invention.

[0036] A geopolymer material prepared in a low-alkali environment, comprising a geopolymer precursor and a low-alkali excitation material, wherein the geopolymer precursor comprises 70-100 parts and the low-alkali excitation material comprises 150-230 parts;

[0037] The low-alkali activating materials include calcined shell powder, alkali slag powder and water, and the geopolymer precursor is a high-aluminosilicate volcanic ash material.

[0038] Among them, 50-80 parts of calcined shell powder; 50-80 parts of alkali residue powder; 50-70 parts of water;

[0039] The geopolymer precursors include but are not limited to metakaolin, slag powder, fly ash and red mud among high aluminosilicate volcanic ash materials.

[0040] In the geopolymer material prepared from solid waste, the geopolymer precursor is slag powder.

[0041] The slag powder is granulated blast furnace slag powder, and the 7-day activity index of the slag powder is greater than 75, and the 28-day activity index is greater than 95.

[0042] The method for preparing geopolymer in a low-alkali environment comprises:

[0043] Step a: Preparation of calcined shell powder

[0044] Rinse the discarded shells and place them in a drying oven, drying them at 105°C for 4-6 hours to remove moisture from the shell surface;

[0045] The dried shells were initially crushed using a jaw crusher, and the crushed shell particles passed through a 5.0 mm sieve;

[0046] The sieved shells are added to a grinder for mechanical grinding until all of them pass through a 0.075 mm sieve to obtain shell powder;

[0047] The shell powder is calcined at a high temperature of 650° C. for 3-5 hours to obtain calcined shell powder, wherein the main components of the calcined shell powder are calcium oxide and calcium carbonate.

[0048] Step b: Preparation of alkali residue powder

[0049] The collected industrial waste alkali residue was dried in a drying oven at 105°C for 4-6 hours to remove moisture;

[0050] The dried alkali residue is put into a grinder for mechanical grinding until all of it passes through a 0.075 mm sieve to obtain alkali residue powder.

[0051] Step c: Preparation of geopolymer from solid waste

[0052] Pour the calcined shell powder and alkali residue powder into a mixing machine according to a certain ratio, dry mix for 3 minutes, add a certain amount of water and stir until uniform to obtain a low-alkali solution;

[0053] Then add granulated blast furnace slag powder to the low-alkali solution and continue stirring for 3-5 minutes until a uniform geopolymer slurry with moderate viscosity is obtained;

[0054] At this time, the calcium hydroxide and calcium bicarbonate generated after the calcium oxide and calcium carbonate in the calcined shell powder dissolve with water provide a weak alkaline solution environment. Compared with the strong alkaline excitation environment of water glass and sodium hydroxide, the geopolymer generated under the weak alkaline environment has similar strength and is not highly corrosive. The soluble salts such as calcium sulfate and calcium chloride contained in the alkaline slag can react with the silicon oxide, aluminum oxide and other components in the slag to generate crystalline hydration products, thereby promoting the development of strength.

[0055] Embodiment 1:

[0056] A low-alkali geopolymer prepared from solid waste comprises the following raw materials in parts by weight: 50 parts of calcined shell powder raw material, 50 parts of alkaline slag powder, 100 parts of granulated blast furnace slag powder and 70 parts of water.

[0057] The above raw materials are used to prepare geopolymer slurry according to the preparation method, and the obtained geopolymer slurry is used to prepare triple 100mm*100mm*100mm geopolymer test blocks;

[0058] The test blocks were cured and subjected to uniaxial compressive strength tests after reaching the curing age. The 3d compressive strength reached 10.6MPa, the 7d compressive strength reached 14.2MPa, and the 28d compressive strength reached 26.1MPa. The specific curing days and strength change trends are shown in Figure 1 shown.

[0059] Embodiment 2:

[0060] A low-alkali geopolymer prepared from solid waste comprises the following raw materials in parts by weight: 65 parts of calcined shell powder raw material, 65 parts of alkali slag powder, 100 parts of granulated blast furnace slag powder, and 70 parts of water.

[0061] The above raw materials are used to prepare geopolymer slurry according to the preparation method, and the obtained geopolymer slurry is used to prepare triple 100mm*100mm*100mm geopolymer test blocks;

[0062] The test blocks were cured and subjected to uniaxial compressive strength tests after reaching the curing age. The 3d compressive strength reached 12.7MPa, the 7d compressive strength reached 18.9MPa, and the 28d compressive strength reached 31.6MPa. The specific curing days and strength change trends are shown in Figure 2 shown.

[0063] Embodiment three:

[0064] A low-alkali geopolymer prepared from solid waste comprises the following raw materials in parts by weight: 80 parts of calcined shell powder raw material, 80 parts of alkaline slag powder, 100 parts of granulated blast furnace slag powder, and 70 parts of water.

[0065] The above raw materials are used to prepare geopolymer slurry according to the preparation method, and the obtained geopolymer slurry is used to prepare triple 100mm*100mm*100mm geopolymer test blocks;

[0066] The test blocks were cured and subjected to uniaxial compressive strength tests after reaching the curing age. The 3d compressive strength reached 14.6MPa, the 7d compressive strength reached 21.7MPa, and the 28d compressive strength reached 35.2MPa. The specific curing days and strength change trends are shown in Figure 3 shown.

[0067] Embodiment 4:

[0068] A low-alkali geopolymer prepared from solid waste comprises the following raw materials in parts by weight: 90 parts of calcined shell powder raw material, 90 parts of alkaline slag powder, 100 parts of granulated blast furnace slag powder, and 70 parts of water.

[0069] The above raw materials are used to prepare geopolymer slurry according to the preparation method, and the obtained geopolymer slurry is used to prepare triple 100mm*100mm*100mm geopolymer test blocks;

[0070] The test blocks were cured and subjected to uniaxial compressive strength tests after reaching the curing age. The 3d compressive strength reached 12.7MPa, the 7d compressive strength reached 19.5MPa, and the 28d compressive strength reached 34.4MPa. It can be seen that when the weight of the low-alkali activated material is further increased, the strength of the prepared test blocks does not increase accordingly.

[0071] Comparative Example 1:

[0072] A high-alkali activated metakaolin-based polymer was used as a comparative example, which included the following raw materials in parts by weight: 160 parts of metakaolin, 11 parts of sodium hydroxide, 71 parts of water glass, and 34 parts of water.

[0073] The metakaolin is obtained by calcining kaolin at 850° C. for 4 hours and then sieving through a 1250 mesh sieve. The purity of sodium hydroxide is ≥99.8%, the water glass modulus is 3.24, and the water glass modulus of the mixed high alkaline stimulating solution is controlled to be 1.3.

[0074] A triple 100mm*100mm*100mm geopolymer test block was prepared using the ratio described in the comparative example. After reaching the curing age, a uniaxial compressive strength test was conducted on it. The 3d compressive strength reached 10.5MPa, the 7d compressive strength reached 12.7MPa, and the 28d compressive strength reached 25.2MPa, all of which were less than.

[0075] Comparative Example 2:

[0076] A high alkaline environment was used to activate iron tailings / metakaolin polymer as a comparative example, which includes the following raw materials in parts by weight: 140 parts of iron tailings, 100 parts of metakaolin, 60 parts of alkaline slag, and 75 parts of high alkaline activation solution.

[0077] The high alkaline stimulating solution is prepared by mixing sodium hydroxide, water glass and water, and the water glass modulus is controlled to be 2.0.

[0078] A triple 100mm*100mm*100mm geopolymer test block was prepared using the ratio described in the comparative example. After reaching the curing age, a uniaxial compressive strength test was carried out on it. The 3d compressive strength reached 14.7MPa, the 7d compressive strength reached 22.7MPa, and the 28d compressive strength reached 33.7MPa.

[0079] Compared with the high alkalinity excitation of iron tailings, metakaolin, and alkaline slag geopolymers in the comparative examples, the present invention uses a weak alkaline environment to excite slag geopolymers. Compared with the former which is excited by a high alkaline environment provided by sodium hydroxide and water glass, the weak alkaline excitation environment of the present invention is provided by calcined shell powder and alkaline slag dissolved in water, which has obvious economic advantages while utilizing waste to purify the environment. At the same time, the geopolymers generated in a weak alkaline environment have similar strength and are not highly corrosive, which can reduce damage to construction equipment and reduce the risk of burns to the human body during the mixing process. Granulated blast furnace slag powder is used as a precursor material to prepare geopolymers, which is inexpensive and also belongs to waste materials generated by industrial development.

[0080] Comparative Example 3:

[0081] A low-alkali environment-activated water-resistant geopolymer was used as a comparative example, which includes the following raw materials in parts by weight: 45.25 parts of aggregate, 1.99 parts of solid sodium silicate particles, 280 parts of sodium aluminate particles, 2.25 parts of reinforcing fiber, 0.11 parts of potassium hydroxide, 1.74 parts of silica sol, and 0.62 parts of active ultrafine alumina powder.

[0082] The mixture was vibrated and pressure-formed under a pressure of 20.0 MPa, and the curing system was as follows: curing at 40°C for 2.5 hours, curing at 70°C for 4 hours, and curing at 100°C for 46 hours to obtain the geopolymer board. After testing, the average bending strength of the board sample was 35.5 MPa, and the flexural strength after high temperature heating to 800°C was 39.9 MPa, and the appearance of the sample was not damaged.

[0083] The low-alkali environment used in the comparative documents to stimulate geopolymers mainly comes from two aspects: 1. Directly reduce the use of the original high-alkali solution, that is, reduce the use of sodium hydroxide and potassium hydroxide. 2. Add substances that can increase the activity of reactants to the original excitation system, such as active ultrafine alumina powder and silica-alumina gel. That is, use highly active substances to make up for the negative impact of alkalinity deficiency. The weak alkaline excitation environment of the present invention is provided by calcined shell parts and alkaline slag dissolved in water. Compared with the use of high alkalinity sodium hydroxide, etc., it mainly reduces the alkalinity of the solution, that is, the concentration of substances per liter of liquid. The soluble salts such as calcium sulfate and calcium chloride contained in the alkaline slag can react with the silicon oxide, aluminum oxide and other components in the slag to generate crystalline hydration products, thereby promoting strength development. Using slag powder as a precursor, its high calcium content can form CHS single-chain gel during the curing process of the geopolymer, so its coagulation time is short, the early strength development is fast, and the negative impact of alkalinity deficiency is compensated. Therefore, this invention can be stimulated under low alkalinity conditions to obtain similar strength development as that stimulated under the original high alkalinity conditions.

[0084] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. These modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention, and they should all be included in the scope of the claims and specification of the present invention.

Claims

1. A geopolymer material prepared in a low-alkali environment, characterized in that: The geopolymer material has the following components by weight: 70-100 parts of geopolymer precursor; 150-230 parts of low-alkali exciting material; Among them, the low-alkali activating material includes calcined shell powder, alkali residue powder and water; The geopolymer precursor is a high aluminosilicate volcanic ash material.

2. The geopolymer material prepared in a low-alkali environment according to claim 1, characterized in that: The low-alkali activating material comprises 50-80 parts of calcined shell powder, 50-80 parts of alkali residue powder, and 50-70 parts of water.

3. The geopolymer material prepared in a low-alkali environment according to claim 1, characterized in that: The geopolymer precursor includes one or more of metakaolin, slag powder, fly ash or red mud in high aluminosilicate volcanic ash materials.

4. The geopolymer material prepared in a low-alkali environment according to claim 3, characterized in that: The slag powder in the high aluminosilicate pozzolanic material is granulated blast furnace slag powder, and the 7-day activity index of the slag powder is greater than 75, and the 28-day activity index is greater than 95.

5. A method for preparing geopolymer in a low-alkali environment, characterized in that: The steps include: Preparation of shell powder The cleaned shells are dried, crushed, and ground, and then calcined at 650°C for 4-5 hours to obtain calcined shell powder; Preparation of alkali residue powder The alkali residue is dried at 105°C for 4-6 hours, put into a grinder, and sieved to obtain alkali residue powder; Geopolymer preparation Pour shell powder and alkali residue powder into a mixing container in a certain proportion, dry mix for 3 minutes, add water and stir until uniform, to obtain a low-alkali excitation solution; Add the geopolymer precursor to the low-alkali activated solution and stir for 3-5 minutes until a geopolymer slurry with a uniform texture is obtained.

6. The method for preparing geopolymer in a low-alkali environment according to claim 5, characterized in that: The shells are washed and dried at 105°C for 5-6 hours, and then initially crushed by a crusher and passed through a 5.0 mm sieve. The sieved shells are ground by a grinder until all pass through a 0.075 mm sieve to obtain shell powder, which is then calcined at high temperature to obtain calcined shell powder. The main components of the calcined shell powder are calcium oxide and calcium carbonate.

7. The method for preparing geopolymer in a low-alkali environment according to claim 5, characterized in that: The alkali residue is ground by a grinder and passed through a 0.075 mm sieve until all of it is sieved to obtain alkali residue powder.

8. The method for preparing geopolymer in a low-alkali environment according to claim 5, characterized in that: The shell powder and alkali residue powder are put into a stirring container at a mass ratio of 1:1 for dry mixing.

9. A geopolymer material prepared in a low-alkali environment of solid waste, the geopolymer material having the components according to the geopolymer material of claim 1 in terms of weight fraction.

Citation Information

Patent Citations

  • Inorganic gel material for decoration engineering

    CN108706892A

  • Preparation method of calcium carbonate type waste residue geopolymer

    CN111592287A

  • Alkali-activated cementing material for inhibiting chemical shrinkage and preparation method thereof

    CN116081968A

  • Cement-free and exciting-agent-free ultrahigh-strength cementing material and preparation method thereof

    CN116283081A

Cited By

  • Single-component alkali-activated engineering residue soil geopolymer as well as preparation method and application thereof

    CN120328895A